Review of the mite genus Gaeolaelaps Evans & Till (Acari: Laelapidae), and description of a new species from North America, G. gillespiei n. sp. - Beaulieu, Frédéric (Zootaxa, 2009)
The concept of the genus Gaeolaelaps of the mite family Laelapidae is reviewed, based on species descriptions in the literature and the examination of specimens of selected described and undescribed species. A short diagnosis and a description of the genus is presented, showing the range of morphological character states and indicating species that depart from the typical character states. Gaeolaelaps is restored from subgeneric to generic rank. A new species, G. gillespiei n. sp., is described from adult female and male specimens. This species shows promise in the control of fungus gnats and thrips on greenhouse cucumbers in British Columbia, Canada. It is a relative of the well known biocontrol agent Gaeolaelaps (or Hypoaspis) aculeifer, but presents a set of morphological traits that distinguish it from G. aculeifer and other related species. The diversity of soil-dwelling mesostigmatic mites remains poorly explored, and so is their potential for biological control.